Renewable energy and CO2 emissions in developing and developed nations: a panel estimate approach - Jie, Wang; Rabnawaz, Khan (Frontiers in Environmental Science, 2024)
Emerging economies and ecosystems are critically dependent on fossil fuels, and a country's energy dependence is a significant measure of its reliance on foreign suppliers. This study evaluates the impact of energy reliance on energy intensity, CO2 emissions intensity, and the utilization of renewable resources in 35 developing and 20 developing nations, as well as the connection between renewable energy, GDP growth, and CO2 emissions. This study employs the Generalized Linear Model (GLM) and the Robust Least Square (RLS) method to assess the inverse association between renewable energy and developed and developing economy policymakers, utilizing unique linear panel estimate approaches . The impact of renewable energy as a response variable on economic growth, energy consumption, and CO2 emissions across four continents is investigated in this study. The findings indicate that developing countries experience a rise in per capita CO2 emissions if their renewable energy use exceeds their capacity. This finding remains significant even when other proxies for renewable energy use are introduced using modified approaches. Furthermore, it is particularly relevant to industrialized nations that possess more developed institutions. Even more surprisingly, in terms of the energy and emissions intensity required for growth, energy dependence has accelerated all components. The regional analysis revealed a spillover impact in most areas, suggesting that the consequences of energy dependence are essentially the same in neighboring countries. The growth of the renewable energy sector and the decrease of greenhouse gas emissions depend critically on the ability of regional energy exchange unions to mitigate the negative environmental and economic impacts of energy dependency. These underdeveloped countries need to spend more on research and development if they want to catch up technologically.